1983
DOI: 10.1111/j.1365-3083.1983.tb00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependence of the IgA Anti‐α(1→3) Dextran B1355 Response in Vitro

Abstract: The magnitude of the Balb/c mouse IgA anti-alpha (1 leads to 3) dextran B1355 (anti-dex) response in vivo was recently found to be markedly T-cell-dependent and age-dependent. This report demonstrates that the in vitro IgA anti-dex response by mesenteric lymph nodes (MLN) is highly age-dependent and that there is an age-dependent increase of the background IgA anti-dex plaque-forming cell (PFC) response occurring in the absence of added antigen which correlates significantly with the magnitude of the antigen-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Since secretary IgA responses in animals appear to have a high degree of T-cell regulation , immunity at mucosal surfaces of the elderly might also be sub-optimal. We (Smith et al, 1983) and others (Rivier et al, 1983) have observed significantly reduced IgA responses to defined antigens in senescent rodents, although Szewcuk and colleagues (1981) found no age-related changes in IgA plaque-forming cells from mesenteric lymph nodes after immunization. Characteristics of secretary antibody in aged humans have not been actively investigated, despite the homeostatic importance of an intact mucosal immune system.…”
Section: Discussionmentioning
confidence: 94%
“…Since secretary IgA responses in animals appear to have a high degree of T-cell regulation , immunity at mucosal surfaces of the elderly might also be sub-optimal. We (Smith et al, 1983) and others (Rivier et al, 1983) have observed significantly reduced IgA responses to defined antigens in senescent rodents, although Szewcuk and colleagues (1981) found no age-related changes in IgA plaque-forming cells from mesenteric lymph nodes after immunization. Characteristics of secretary antibody in aged humans have not been actively investigated, despite the homeostatic importance of an intact mucosal immune system.…”
Section: Discussionmentioning
confidence: 94%
“…For example, in mice, mesenteric lymph node responses to antigens such as trinitrophenol (TNP)-bacillus Calmette-Guerin (Szewczuk et al, 1981), the α(1-3) glucan determinant on dextran B1355 (Rivier et al, 1983), and TNP-keyhole limpet hemocyanin (Wade and Szewczuk, 1984) are unaffected by age. The most significant observation in aged animals is that antigen-specific B cell responses to cholera toxin at mucosal effector sites are lower than in healthy adults .…”
Section: Mucosal Immune Systemmentioning
confidence: 99%
“…Allotype-dependent differences in IgG3 concentrations are measurable in some children as early as 6 months of age (164), whereas allotype differences in IgG2 concentrations can be difficult to quantitate before 5 years of age (173). In children, the combination of being Gm-f negative (and subsequently having suboptimal IgG3 levels [21,164,170,223]) and G2m(n) negative may have more significance on predisposition to infection by noncapsulated bacteria than being solely G2m(n) negative. This is demonstrated in studies involving Branhamella catarrhalis, a noncapsulated gram-negative organism, which preferentially causes otitis media in young children with Gm phenotype-linked IgG3 deficiencies (21,65).…”
Section: Role Of Immunodeficiency and Allotypementioning
confidence: 99%
“…The IgA response to polysaccharide antigen is also highly age dependent, especially when an animal is primed via the gastrointestinal system (170). Unlike the Gm haplotypes mentioned above, the frequencies of A2m allotypes are race dependent (203).…”
Section: Role Of Immunodeficiency and Allotypementioning
confidence: 99%